IMPLMENTASI PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA KELAS VIII DISMP MA’ARIF IRSYADUL MUNTADI IEN KALIWIRO WONOSOBO - Anita; Rifki Muntaqo; Ali Imron (JOURNAL SAINS STUDENT RESEARCH, 2025)
he Pancasila Student Profile serves as a fundamental framework for character development among Indonesian students in the 21st century. It encompasses six essential dimensions: faith and devotion to God Almighty alongside noble character, global diversity, mutual cooperation, independence,critical thinking,and creativity.This study employed a descriptive qualitative approach, utilizing data collection methods such as observation,interviews, and documentation. The findings indicate that the integration of these six dimensions has been implemented in the Islamic Religious Education (PAI) learning process, covering the stages of planning, implementation, and evaluation. Teachers employ instructional methods such as discovery learning and project-based learning to foster student character. Although the implementation is generally effective supported by teacher training and value-based activities challenges remain, including limited infrastructure,diverse student characteristics,and budget constraints. Therefore,there is a need for strategies that strengthen facilities,adopt adaptive teaching approaches,and enhance external collaboration to optimize character development through PAI.